Getting the message: Communications workers and global value chains. (1st October 2010) - ,; ,
Abstract : This introductory essay addresses the meaning of terms like ''knowledge'', ''communications'' and ''cultural'' labour in an era of increasingly global value chains. It takes up different ways to think about such labour, ranging from mainly creative work to work anywhere in the value chain that produces communication and information technology, and from one side of the creative/technical divide to the other. It also considers the changing relationship of these forms of labour to global capitalism. The essay concludes that knowledge workers are learning a lot from one another and are using what they learn to unite in many interesting ways.